Post‐storm sediment burial and herbivory of Vallisneria americana in the Hudson River estuary: mechanisms of loss and implications for restoration. Issue 4 (12th January 2017) - Hamberg, Jonas; Findlay, Stuart E. G.; Limburg, Karin E.; Diemont, Stewart A. W.
Abstract: This article investigates the mechanics of loss of Hudson River Vallisneria americana after the high volume storms at the end of the 2011 growing season, when two severe weather events—Tropical Storm Irene and the remnants of Tropical Storm Lee—struck the Hudson River watershed. In 2012, the distribution of the most common species of submerged aquatic vegetation (SAV), Vallisneria americana (wild celery, water celery, or tape grass), in the Hudson River estuary declined by more than 90%, with no appreciable recovery in 2013 and 2014. Because of its important habitat value for aquatic life and for increasing dissolved oxygen, managers and scientists have begun discussing the reasons for the loss, as well as how to assist its recovery through assisted restoration efforts in the estuary. Supported by in situ and in vitro experiments, the article posits the hypothesis that sediment, washed into the river by the storm, buried overwintering tubers of the plant, thus reducing sprouting success. Sprouting was as low as 50% with sediment depth between 2 and 5 cm; sprouting did not occur with sediment depth greater than 10 cm. Field experiments found no support for the hypothesis that herbivory inhibited regrowth of the plant after the storm events. These results suggest that future assisted restoration of Vallisneria americana and SAV in general may require attention to system‐specific factors.